A Hemangioma of the Zygomatic Bone: Management Ensuring Good Reconstructive and Aesthetic Results. Issue 4 (December 2017) - Bocchialini, Gabriele; Castellani, Andrea; Bozzola, Anna; Rossi, Alessandro
Hemangiomas are benign tumors representing only 0.7 to 1% of all bone tumors; those that arise in the zygomatic region are rarely described in the literature. Here, we describe the case of a 55-year-old woman with a mass in the right orbitozygomatic region. She was diagnosed on the basis of preoperative clinical manifestations, data from an earlier histopathological examination, and computed tomography (CT). The CT scan revealed a lesion in the right zygomatic region at the level of the cancellous component. This caused thinning and remodeling of the deformed cortex both medially and laterally. Surgery was performed. We describe the clinical characteristics of our case with an emphasis on surgical management of the lesion using a titanium grid prepared by reference to a stereolithographic model.